Reduction of the Ca2+ permeability of ligand-gated ion channels as a strategy against excitotoxicity - D’Andrea, Tiziano; Fucile, Sergio (Frontiers in Cellular Neuroscience, 2025)
Excitotoxic damage is due to an excessive Ca2+ entry in cells following overactivation of Ca2+-permeable ion channels. In neurons, Ca2+-dependent excitotoxicity is linked to the prominent activation of N-Methyl-d-Aspartate receptors (NMDARs), exhibiting a high permeability to Ca2+. Different neurodegenerative diseases share glutamate-and NMDAR-dependent excitotoxicity as a pathogenic mechanism, but also different ligand-gated ion channels (LGICs) may be involved in excitotoxic-related pathologies, such as muscle nicotinic acetylcholine receptor in some forms of congenital myasthenic syndrome. We posit that excitotoxicity due to the overactivation of Ca2+-permeable LGICs may be counteracted by using molecules able to reduce selectively the Ca2+ entry, without blocking Na+ influx, thus reducing the adverse effects induced by channel blockers. In this review, we recapitulate: (i) the techniques used to quantify the Ca2+ permeability of LGICs, with a particular focus on the fractional Ca2+ current (Pf, i.e., the percentage of the total current carried by Ca2+); (ii) the known Pf values of the main LGICs; (iii) the modulation of the LGIC Pf values induced by drugs and measured to date. These data support the possibility of fighting excitotoxicity-related pathologies with a new therapeutic approach.